Stakeholders’ Perceptions of an English for Occupational Purposes Course - Sarudin, Isarji; Zainab Mohd Noor,, Zainab; Amal Mechraoui,, Amal; Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Abdul Malik, Faridah (© IDOSI Publications, 2013, 2013)
As the business world is becoming increasingly global and competitive, most business organizations require employees to have good employability skills. In order to ensure employees are equipped with relevant employability skills, the industry turns to higher education for assistance. One initiative of higher education institutions is to offer English for Occupational Purposes (EOP) courses. This study was undertaken to investigate the strengths and weaknesses of English for Occupational Purposes course for students of Economics and Management Science based on internal stakeholders’ perceptions. A multi-method approach was adopted and triangulation of methods comprising survey questionnaires and semi-structured interviews were employed. A total of 177 respondents consisted of undergraduate students, instructors and academic administrators of the EOP course participated in the study. The findings of this study revealed that the students, instructors and academic administrators, in general were satisfied with the EOP course. However, there were shortcomings that need to be addressed, particularly related to methods of teaching and oral and written communication skills related to job application. Key words: English language proficiency Employability English for Occupational Purposes Higher education institutions